Culture, patience, and lifelong learning how institutional design can support continued education - Jasmin Vietz (EconPol Forum, 2026)
Lifelong learning is key for long-term economic development. Patience drives adults' participation in continued education. Cultural traits shape learning behavior across generations. Policy can offset motivational gaps by reducing immediate costs and combining short-term recognition with long-term qualification.
Keywords: 330